Entanglement and correlation properties of exciton-polaritons in semiconductor microcavities (2015)
Abstract. Polariton, the quasiparticle emerging from the strong coupling between light and matter in semiconductor microcavities has shown to be a good candidate for applications in quantum information processing devices, and in the last years has become the cornerstone of the solid state realization of quantum computation. The necessary condition that endows these protocols with remarkable advantages over their classical counterparts is the so called entanglement or non separability of states, an exclusive property of quantum mechanical systems. The present thesis is a compilation of three theoretical works about the quantum properties of semiconductor microcavity-quantum dot systems. In each case a model of a two level system interacting with a single electromagnetic mode of the microcavity via dipolar interaction is used. First of all, we study the case of a single quantum dot embedded in an optical microcavity by using a dissipative Jaynes-Cummings model. Two non coherent processes are considered: photon leakage through the cavity walls and exciton pumping. The steady state of the system is calculated in a master equation formalism, then mixedness and entanglement are quantified through linear entropy and negativity, respectively. In particular we find the set of parameters that maximizes light-matter entanglement and purity in the system. Then, an extension to the multiple non interacting quantum dots case is made. In the second work, we analyze the possibility of change the incoherent exciton pumping for a non dissipative matter pumping mechanism in order to study if it favors the non separability of the subsystems. Again, we find the set of parameters that maximize light-matter entanglement and purity of the system in its steady state. A comparison with a maximally entangled (Bell) state is performed with aid of the fidelity criteria. Finally, an extension to the case of interacting quantum dots is made by using a Tavis-Cummings model with a dot-dot interaction term. As a first approach to the complete problem, the entanglement of the eigenstates of the hamiltonian is quantified through the concurrence criteria.